Analisis Struktur, Isi, dan Diksi Teks Deskripsi Siswa Kelas VII SMP Negeri 1 Enam Lingkung - Ena Noveria; Endah Saputri Neli (Universitas Negeri Padang, 2021)
The purpose of this research is to describe the following three things. First, describe the structure of the descriptive text of class VII students of SMP Negeri 1 Enam Lingkung. Second, to describe the contents of the descriptive text of class VII students of SMP Negeri 1 Enam Lingkung. Third, describe the diction of the descriptive text of class VII students of SMP Negeri 1 Enam Lingkung. The type of research used is qualitative research with descriptive methods. The data in this study are in the form of structure, content, and diction of student description texts. The data source of this research is the descriptive text of the seventh grade students of SMP Negeri 1 Enam Lingkung for the academic year 2021/2022 with a total of 25 students.Based on the results of the study, it can be concluded three things. First, in writing descriptive texts, seventh grade students of SMP Negeri 1 Enam Lingkung have used all three descriptive text structures. Second, in terms of content, the descriptive text of grade VII students of SMP Negeri 1 Enam Lingkung has written the contents according to the structure of the descriptive text. Third, judging from the use of diction, the descriptive text of class VII students of SMP Negeri 1 Enam Lingkung is more dominant in the accuracy of diction in the descriptive text of the seventh grade students of SMP Negeri 1 Enam Lingkung.Keywords: structure, content, diction of description text